Effects of Intradialytic Exercise on Adequacy, Depression, and Quality of Life in Hemodialysis Patients - Gusti Ayu Ary Antari; Devia Putri Lenggogeni (NERS Jurnal Keperawatan, 2025)
There are three independent predictors related to dialysis mortality rates such as adequacy, depression and poor quality of life. Intradialytic exercises are a potential strategy to increase adequacy, overcome depression and improve quality of life. This study aimed to analyse the effectiveness of intradialytic exercise in addressing adequacy, depression, and quality of life. A quasi-experimental design was used in this study. The study was conducted at a hemodialysis clinic in Bali, from August to October 2020. A total of 60 samples involved in the research were selected using purposive sampling. Samples were randomly grouped into intervention (n = 30) and control (n = 30) groups. Patients in the intervention group were given intradialytic exercises for 30 minutes/day twice a week for four weeks. All patients underwent measurement of adequacy using Kt/V, depression using the Beck Depression Inventory-II and quality of life using Kidney Disease Quality of Life. Measurements were taken at baseline and after four weeks. The results showed there was a decrease in the mean depression score in patients after being given intradialytic exercise (p-value = 0.001). Intradialytic exercise significantly affects adequacy (p-value = 0.003). Regarding quality of life, this study did not find any significant effect from intradialytic exercises, but there was an increase in the average score on the mental health composite dimension. This study concludes that intradialytic exercise can be considered a therapeutic modality applied routinely in hemodialysis rooms. Apart from that, exercise is also safe, and there are no reports of side effects from exercise.